PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN MEMECAHKAN MASALAH DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL SEKOLAH DASAR - Sinta Maria Dewi; Haerudin Haerudin; Siti Hasanah; Danial Kusumah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine the Problem Based Learning (PBL) Learning Model on the Social Science Problem Solving Ability of Elementary School Students. The method used in this research is the method of Pre-Experimental Design with a One-Group-Pretest-Posttest Design research design. This study's findings indicate that the average post-test is higher than the pretest average of students' social studies problem-solving abilities with the Problem Based Learning (PBL) learning model. The average pretest value is 58.10, while the post-test average value is 75.40. Calculation of the hypothesis using the t-test, namely the paired sample T-test, and obtained at a significant level of 0.05 indicates that the probability value (significance) is 0.000. Because the significance of 0.000 <α = 0.05, Ho is rejected. This proves that there is an effect of the Problem Based Learning (PBL) learning model on solving elementary school students' social studies problems.